A Logical Approach to Philosophy Essays in Honour of Graham Solomon - DeVidi, David; Kenyon, Tim (The Western Ontario Series in Philosophy of Science, A Series of Books in Philosophy of Science, Methodology, Epistemology, Logic, History of Science, and Related Fields, 2006)
The papers in this collection are united by an approach to philosophy. They illustrate the manifold contributions that logic makes to philosophical progress, both by the application of formal methods to traditional philosophical problems and by opening up new avenues of inquiry as philosophers sort out the implications of new and often surprising technical results. Contributions include new technical results rich with philosophical significance for contemporary metaphysics, attempts to diagnose the philosophical significance of some recent technical results, philosophically motivated proposals for new approaches to negation, investigations in the history and philosophy of logic, and contributions to epistemology and philosophy of science that make essential use of logical techniques and results. Where the work is formal, the motives are obviously philosophical, not merely mathematical. Where the work is less formal, it is deeply informed by the relevant formal material. The volume includes contributions from some of the most interesting philosophers now working in philosophical logic, philosophy of logic, epistemology and metaphysics.